Reader as a Character’s Interlocutor in J. Barnes’ Postmodernist Texts (Proceedings of Southern Federal University. Philology, 2018)
Anastasia A. Borovkova (Rostov-on-Don, Russian Federation)The texts of both novels are characterized by a notable lack of the narrator figure, which would have acted as an intermediary between the narrative and the readers, the imagined text world and the real world actors who perceive these works of art. In fact, both texts resemble the play script, which reveals a direct dialogue on several levels at once-between imaginary characters and the implied readers, the characters themselves and the fictional world of novel texts, the author and the real reader. The absence of an intermediary narrator in a literary – especially postmodern – work is not an innovation. J. Barnes eliminates the possibility of any system of ideas «behind the stage» voice, the author’s interpretation of the text. The basic organizational unit of the texts analyzed by us is not so much the chapter, as a kind of initial replica, consisting of a narrative character at some point unfolding the text storyline. The recipient of such remarks is the reader.The imaginary world, which «blooms» in front of the reader’s eyes, is perceived as a primordial one, which does not even suggest a non-viscous conductor. In the absence of the narrator the narrative world is multi-faceted objectified in the text of novels based on the dialogical relationships between the characters and their addressees. The reader begins to perceive itself as a full participant in the communication that takes place between characters. In the texts of the two novels everything shows dependence on the flowing dialogical processes – starting with the title of the first novel and ending with the factor that the characters live and act solely as the narrative voices. Although, at first glance, it may seem that the novel texts are designed with the sequences of matched inner monologues and the general narrative matrix is a dialogic, the sources of which are usually three characters.Key words: reader, character, postmodernist fiction interpretation, narrative technique, communicative style, dialogic interaction.DOI 10.23683/1995-0640-2018-3-33-40